PREFERENSI PELAKU USAHA PADA E-COMMERCE TERHADAP LAYANAN LAST MILE DELIVERY - Rachmawati, Ika; Utama, Adiguna Sasama Wahyu; Ruhana, Nafisah (Politeknik Negeri Ambon, 2025)
Introduction: Last-mile delivery is the critical final stage of the logistics chain, delivering goods from local distribution centers to end consumers and playing a pivotal role in customer satisfaction. To maintain buyer satisfaction and loyalty, e-commerce merchants must select courier service providers with established reputations and proven reliability. This study examines seller preferences regarding courier services, explicitly focusing on last-mile delivery operations.Methods: This research engaged a quantitative approach applying survey methodology. Data collection was conducted through both offline and online questionnaire distribution. The sample comprised 187 e-commerce store owners domiciled in East Java Province, Indonesia. Data analysis was performed using SmartPLS. Results: The findings reveal that performance expectancy in delivery reliability, delivery mode, and delivery cost significantly influences intention to use courier services. Performance expectancy in delivery time emerged as the most dominant factor, demonstrating significant effects both directly on intention to use and indirectly through performance expectancy in delivery cost as a mediating variable. Conversely, performance expectancy in the delivery area did not significantly affect intention to use.Conclusion and suggestion: The findings underscore that courier service providers must prioritize delivery reliability, cost efficiency, mode flexibility, and delivery speed, as these factors constitute primary considerations for e-commerce sellers when selecting last-mile delivery services for customer fulfillment. Future research should expand the scope of investigation and conduct segmented analysis by categorizing sellers by e-commerce platform. The inclusion of variables such as platform-specific internal policies is warranted, given that specific e-commerce platforms operate proprietary integrated logistics services. Keywords: Last-mile, Delivery, Customer, Preference, Service